The Relationship Between Training Frequency and Tennis Elbow Injuries in Tennis Players - Felix Nashar Novanto; Anita Faradilla Rahim; Dimas Sondang Irawan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Tennis is a sport that uses rackets and can be played by two or four players. Forehand, backhand, and serve shots are some of the methods used to hit the ball while playing tennis. Constantly hitting the ball with a racket can strain the hand, increasing the risk of tennis elbow injury. Because it often affects tennis players, the term “tennis elbow” is used. To succeed and excel, an athlete must exercise and have optimal body shape. A combination of the three elements of exercise duration, frequency, and intensity is necessary to obtain training results. Training methods, specifically training frequency, intensity and duration, have a significant impact on player health. Biomechanical movements and high weekly training frequency make athletes vulnerable to injury, one of the diseases that often affect tennis players is tennis elbow. The purpose of this study was to ascertain the relationship between training frequency and tennis elbow injuries experienced by tennis players. Observational analytic research design and quantitative methods were used in this study. The approach used was cross-sectional research. A purposive sample approach, which considers many factors, was used to select 27 tennis players in Malang City who became the study population. In this study, training frequency is the independent variable and tennis elbow injury is the dependent variable. In this study, Cozen's test and questionnaire were used to evaluate tennis elbow. Using Spearman's test for statistical testing, a P value of 0.381 was found. In this case, the p value was greater than ? (0.05). The conclusion of this study is that there is no relationship between training frequency and tennis elbow injury.